Peningkatan Kemampuan Sains Anak melalui Metode Eksperimen Kelompok A di TK Negeri Pembina Kota Mojokerto - Diah Safira Laily; Nur Ika Sari Rakhmawati (Departement of Mathematics Education, 2023)
The type of research used in this study was classroom action research, while the background of the problem in this study was that children's science abilities were still lacking and low in group A1 at Pembina State Kindergarten, Mojokerto City. The purpose of this study was to improve children's science skills through experimental methods in group A at Pembina State Kindergarten, Mojokerto City. The research method used is the PTK design which consists of four stages, namely planning, action, observation, and reflection. The research was conducted in two cycles with four meetings. Subjects in this study consisted of 15 children. Data collection techniques using observation and documentation.The results showed that in the first cycle the results of the child's scientific ability through the experimental method were 52.9%. This shows that this classroom action research has not been successful. So it requires action again in cycle II. The results of the research in cycle II showed that children's scientific abilities increased by 76.8%. Based on the results of this study, it can be concluded that the experimental method can improve the scientific ability of group A children in TK Negeri Pembina Kota Mojokerto.